A good kind of trouble eaudiobook - Ramée, Lisa Moore (2019)
From debut author Lisa Moore Ramée comes this funny and big-hearted debut middle grade novel about friendship, family, and standing up for what's right, perfect for fans of Angie Thomas's The Hate U Give and the novels of Renée Watson and Jason Reynolds. Twelve-year-old Shayla is allergic to trouble. All she wants to do is to follow the rules. (Oh, and she'd also like to make it through seventh grade with her best friendships intact, learn to run track, and have a cute boy see past her giant forehead.) But in junior high, it's like all the rules have changed. Now she's suddenly questioning who her best friends are and some people at school are saying she's not black enough. Wait, what? Shay's sister, Hana, is involved in Black Lives Matter, but Shay doesn't think that's for her. After experiencing a powerful protest, though, Shay decides some rules are worth breaking. She starts wearing an armband to school in support of the Black Lives movement. Soon everyone is taking sides. And she is given an ultimatum. Shay is scared to do the wrong thing (and even more scared to do the right thing), but if she doesn't face her fear, she'll be forever tripping over the next hurdle. Now that's trouble, for real. ""Tensions are high over the trial of a police officer who shot an unarmed Black man. When the officer is set free, and Shay goes with her family to a silent protest, she starts to see that some trouble is worth making."" (Publishers Weekly, ""An Anti-Racist Children's and YA Reading List"")